2021
DOI: 10.1093/gerona/glab070
|View full text |Cite
|
Sign up to set email alerts
|

Aging Changes in Bladder Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels Are Associated With Increasing Heterogeneity of Adrenergic/Mucosal Influence on Detrusor Control in the Mouse

Abstract: A geroscience-informed approach to the increasing prevalence of bladder control problems in older adults requires understanding the impact of aging on dynamic mechanisms that ensure resilience in response to stressors challenging asymptomatic voluntary control over urine storage and voiding. Bladder control is predicated on sensory neural information about bladder volume. Modulation of volume-induced bladder wall tensions by autonomic and mucosal factors controls neural sensitivity to bladder volume. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Conceptual work highlights resilience with respect to female urinary microbiota 81 and age‐related changes to bladder function 82 . Indeed, Hardy and colleagues suggest that age‐related changes to bladder function are due to loss of resilience as opposed to emerging pathology 83 . It is plausible that neuropsychological resilience in the context of stress would confer some protection from the development of OAB and UI; however, research is needed to test this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Conceptual work highlights resilience with respect to female urinary microbiota 81 and age‐related changes to bladder function 82 . Indeed, Hardy and colleagues suggest that age‐related changes to bladder function are due to loss of resilience as opposed to emerging pathology 83 . It is plausible that neuropsychological resilience in the context of stress would confer some protection from the development of OAB and UI; however, research is needed to test this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Response heterogeneity has been previously associated with alterations in ion channel expression, as variances about mean responses to adrenergic stimuli in strip studies paralleled decreasing expression of Hcn1 , encoding the hyperpolarization‐activated cyclic nucleotide‐gated channel 1 protein (Hardy et al, 2021 ), which has previously been shown to play an important role in adrenergic detrusor tension control with aging in B6 mice (Al‐Naggar et al, 2019 ; Lemtiri‐Chlieh et al, 2022 ; Mader et al, 2018 ; Singh et al, 2022 ). Apart from tissue‐level responses, heterogeneity is also exhibited in response to the stressor of cystometry.…”
Section: Changes With Aging Along the Brain–bladder ...mentioning
confidence: 95%
“…In B6 mice, expression of muscarinic and adrenergic receptors have been reported to decrease with aging (Kamei et al, 2018 ). Decreased receptor expression may provide insight into the decreased responses to excitatory and relaxatory stimuli seen in aged bladder strips from B6 mice (Hardy et al, 2019 , 2021 ), Sprague–Dawley rats (Durlu‐Kandilci et al, 2015 ), and humans (Yoshida et al, 2001 ). Increased agrin—an essential element of the neuromuscular junction—is observed at the neuromuscular junctions of the developing rodent bladder (Gingras et al, 2005 ) and is required for neuromuscular junction integrity (Hoch, 1999 ).…”
Section: Changes With Aging Along the Brain–bladder ...mentioning
confidence: 99%
“…Но природа неумолима, и с прекращением репродуктивной функции наступают изменения физиологии и функций многих клеток. Мы рассмотрим мочеполовую систему, а точнее -мочевой пузырь и влагалище, имеющие единую онто-филогенетическую природу и зависимость от эстрогенов [3][4][5]. Что происходит с мочевым пузырем в менопаузу?…”
Section: влияние менопаузы на мочевой пузырьunclassified